Development of popular scientific books on the diversity of the Cyprinidae family in the Lake Sari Embun Area, Tanah Laut Regency - Nur Alita Yulianti; Dharmono Dharmono; Nurul Hidayati Utami (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
Sari Embun Lake is one of the areas in Tanah Laut Regency with various fish species that have potential as supporting material for local potential-based animal ecology courses. This study aims to describe the diversity of the Cyprinidae family found in the Lake Sari Embun area of Tanah Laut Regency, the process of developing a popular scientific book (PSB) on the diversity of the Cyprinidae family in the Lake Sari Embun area of Tanah Laut Regency, and the feasibility of the developed PSB, including its validity and readability. The research method used is research and development through the Plomp model. The results showed six fish species from the Cyprinidae family, namely seluang langkai (Rasbora argyrotaenia), puyau sangin (Cyclocheilichthys armatus), adungan fish (Hampala macrolepidota), white lampam fish (Barbodes gonionotus), red lampam fish (Barbodes schwanenfeldii), and babuluhan fish (Osteochilus hasselti), with a diversity index of 1.42 (medium diversity category). The PSB development process has the following characteristics: attractive appearance featuring original research images; the material described is data based on research results. The PSB validity results have a score of 3.67 with a very valid category, and the readability test results are 93.06% with very good criteria. Based on the test results, the PSB product for the diversity of the Cyprinidae family in the Sari Embun Lake area in Tanah Laut Regency is procedurally feasible for use as supporting material for the animal ecology course. Abstrak. Danau Sari Embun merupakan salah satu kawasan di Kabupaten Tanah Laut yang memiliki keanekaragaman jenis ikan yang berpotensi sebagai bahan pendukung mata kuliah ekologi hewan berbasis potensi lokal. Penelitian ini bertujuan untuk mendeskripsikan keanekaragaman famili Cyprinidae yang terdapat di kawasan Danau Sari Embun Kabupaten Tanah Laut, proses pengembangan buku ilmiah populer (BIP) keanekaragaman famili Cyprinidae di kawasan Danau Sari Embun Kabupaten Tanah Laut, dan kelayakan BIP yang dikembangkan, meliputi kevalidan dan keterbacaan. Metode penelitian yang digunakan adalah penelitian dan pengembangan melalui model Plomp. Hasil penelitian menunjukkan enam spesies ikan dari famili Cyprinidae, yaitu seluang langkai (Rasbora argyrotaenia), puyau sangin (Cyclocheilichthys armatus), ikan adungan (Hampala macrolepidota), ikan lampam putih (Barbodes gonionotus), ikan lampam merah (Barbodes schwanenfeldii), dan ikan babuluhan (Osteochilus hasselti), dengan indeks keanekaragaman 1,42 (kategori keanekaragaman sedang). Proses pengembangan BIP memiliki karakteristik sebagai berikut: tampilan yang menarik dengan menampilkan gambar-gambar asli hasil penelitian; materi yang dijelaskan merupakan data berdasarkan hasil penelitian. Hasil validitas BIP memiliki skor 3,67 dengan kategori sangat valid, dan hasil uji keterbacaan sebesar 93,06% dengan kriteria sangat baik. Berdasarkan hasil uji coba tersebut, maka produk BIP keanekaragaman famili Cyprinidae di kawasan Danau Sari Embun Kabupaten Tanah Laut secara procedural layak digunakan sebagai bahan ajar pendukung pada mata kuliah ekologi hewan.